Pembelajaran PKn Berbasis Media Digital Sebagai Upaya Pengembangan Karakter Siswa Sekolah Dasar: Pendekatan Kualitatif Deskriptif - Dinar Ayu Mirunggan Sari; Rynaldi Setya Rachim; Dwi Kurniawan (Penerbit Widina, Widina Media Utama, 2026)
Civic Education (PKn) learning in elementary schools is expected not only to deliver civic knowledge but also to foster students’ character development in a meaningful way. However, student participation in PKn learning remains limited, indicating the need for more contextual and innovative learning approaches. This study aims to describe the implementation of digital media–based PKn learning as an effort to support character development among elementary school students. The study employed a descriptive qualitative approach involving teachers and students from an elementary school as research participants. Data were collected through classroom observations, analysis of instructional documents, and reflective evaluation of the learning process. The findings indicate that the integration of digital media in PKn learning enhances students’ active participation, encourages interaction and collaboration, and promotes responsibility and discipline during learning activities. Students showed greater confidence in expressing their ideas and were more actively engaged in group work. In addition, the learning environment became more conducive and student-centered. The study highlights the crucial role of teachers in designing and managing digital media–based learning to ensure alignment with instructional objectives and character education goals. This research provides a practical contribution by offering insights into the use of digital media as an alternative strategy to improve the quality of PKn learning while supporting character development in elementary school students.ABSTRAKPembelajaran Pendidikan Kewarganegaraan (PKn) di Sekolah Dasar dituntut tidak hanya menyampaikan materi kewarganegaraan, tetapi juga mampu menumbuhkan nilai-nilai karakter siswa secara bermakna. Namun, dalam praktiknya, keterlibatan siswa dalam pembelajaran PKn masih relatif terbatas sehingga diperlukan pendekatan yang lebih kontekstual dan inovatif. Penelitian ini bertujuan untuk menggambarkan pelaksanaan pembelajaran PKn berbasis media digital sebagai upaya pengembangan karakter siswa Sekolah Dasar. Penelitian menggunakan pendekatan kualitatif deskriptif dengan melibatkan guru dan siswa pada salah satu Sekolah Dasar sebagai subjek penelitian. Data dikumpulkan melalui observasi kegiatan pembelajaran, analisis dokumen pembelajaran, serta refleksi terhadap proses belajar mengajar. Hasil penelitian menunjukkan bahwa penggunaan media digital dalam pembelajaran PKn mampu meningkatkan partisipasi aktif siswa, mendorong interaksi dan kerja sama antarsiswa, serta menumbuhkan sikap tanggung jawab dan kedisiplinan selama proses pembelajaran. Siswa tampak lebih berani mengemukakan pendapat dan terlibat secara aktif dalam kegiatan kelompok. Selain itu, pembelajaran berlangsung lebih kondusif dan berorientasi pada siswa. Temuan penelitian ini menegaskan bahwa keberhasilan pembelajaran PKn berbasis media digital sangat dipengaruhi oleh peran guru dalam merancang dan mengelola pembelajaran secara pedagogis. Penelitian ini memberikan kontribusi praktis berupa pemahaman tentang pemanfaatan media digital sebagai strategi pembelajaran PKn yang berpotensi meningkatkan kualitas proses pembelajaran sekaligus mendukung pengembangan karakter siswa Sekolah Dasar.